(untitled) (Research, Society and Development, 2022)
Introduction: Diabetes Mellitus is a disease that affects a significant part of the Brazilian population and even with so much research and advances aimed at drug therapy, its treatment is still seen as a major problem for people with this condition. This vision and the characteristics inherent to the treatment make it difficult to adhere to drug therapy. Objective: the objective is to identify factors that interfere with adherence to pharmacological treatment in patients with Diabetes Mellitus 2, through a bibliographical review of the literature. Methodology: Integrative, bibliographical literature review with research in the Scientific Electronic Library Online and Latin American and Caribbean Literature in Health Sciences databases based on the descriptors: Adherence to treatment; Diabetes Mellitus and Drug Therapy. Inclusion criteria, articles published from 2015 onwards, in Portuguese, English and Spanish, and exclusion criteria: other literature reviews, monographs, course conclusion work, master’s and doctoral theses, as well as case reports. Results: 10211 were found in the selected databases, resulting in 24 articles after applying the selection criteria. Conclusion: Factors such as the complexity of drug therapy, metabolic rates, mental health and social issues such as beliefs and illiteracy come into question in the debate on adherence to drug therapy. Adherence to drug therapy is strongly influenced by the diabetes treatment protocol and the patient’s reality.